A companion to medieval Genoa
1 online resource (xxvii, 560 pages)
Keywords: A Companion to Medieval Genoa introduces non-specialists to recent scholarship on the vibrant and source-rich medieval history of Genoa. Focusing mostly on the eleventh to fifteenth centuries, the volume positions the city of Genoa and the Genoese within the broader history of the Italian peninsula and the Mediterranean in the Middle Ages. Thematic contributions highlight the interdependence of local, regional, and international concerns, and serve as a helpful corrective to the traditional overemphasis of Florence and Venice in the English-language historiography of medieval Italy. The volume thus offers a fresh perspective on the history of medieval Italy—as well as a handy introduction to the riches of the Genoese archives—to undergraduates, graduate students, and scholars in related fields. Contributors are Ross Balzaretti, Carrie E. Beneš, Denise Bezzina, Roberta Braccia, Luca Filangieri, George L. Gorse, Paola Guglielmotti, Thomas Kirk, Sandra Macchiavello, Merav Mack, Jeffrey Miner, Rebecca Müller, Antonio Musarra, Sandra Origone, Giovanna Petti Balbi, Valeria Polonio, Gervase Rosser, Antonella Rovere, Stefan Stantchev, and Carlo Taviani.